2022
DOI: 10.1093/oncolo/oyac116
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Efficacy and Tolerability of Brigatinib in Patients with Non-Small Cell Lung Cancer with Prior ALK-TKIs in the United States

Abstract: Background Real-world evidence for brigatinib, a next-generation anaplastic lymphoma kinase-tyrosine kinase inhibitor (ALK-TKI) used in ALK-rearranged non-small cell lung cancer, is scarce. This retrospective study evaluated real-world brigatinib utilization in the US post other ALK-TKIs. Materials and Methods Adults with ≥1 brigatinib claim (index date) between 1 April 2017 and 30 September 2020 in the IQVIA longitudinal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Most patients in the current study (88.5%) reached the full dose of brigatinib (180 mg/day), and most patients (93.1%) were adherent to treatment. This is consistent with a US real‐world study (in which >80% had received a prior ALK inhibitor), where 77% of patients reached brigatinib 180 mg/day and 92.7% of patients were adherent 13 . The probability of continuing brigatinib therapy at 1 year in the current study (63.2%) was higher than when it was administered as second‐line therapy in the global expanded access programme (49.3%) or as second or later line therapy in the US (45%) and Latin American (59.9%) real‐world studies 13,15,16 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most patients in the current study (88.5%) reached the full dose of brigatinib (180 mg/day), and most patients (93.1%) were adherent to treatment. This is consistent with a US real‐world study (in which >80% had received a prior ALK inhibitor), where 77% of patients reached brigatinib 180 mg/day and 92.7% of patients were adherent 13 . The probability of continuing brigatinib therapy at 1 year in the current study (63.2%) was higher than when it was administered as second‐line therapy in the global expanded access programme (49.3%) or as second or later line therapy in the US (45%) and Latin American (59.9%) real‐world studies 13,15,16 .…”
Section: Discussionsupporting
confidence: 89%
“…13 The probability of continuing brigatinib therapy at 1 year in the current study (63.2%) was higher than when it was administered as second-line therapy in the global expanded access programme (49.3%) or as second or later line therapy in the US (45%) and Latin American (59.9%) real-world studies. 13,15,16 It is possible this could indicate a difference between Asian and non-Asian populations, which would be consistent with the ALTA-1 L clinical trial of brigatinib in ALK inhibitor-naïve patients, which found that PFS was longer in Asian than in non-Asian patients, 37 although no notable difference in PFS was found between these subgroups in the ALTA trial in crizotinibrefractory patients. 10 The current study also assessed TTDR and found a reasonably high probability of continuation on the maximum/peak dose of brigatinib at both 1 and 2 years.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Additionally, brigatinib has demonstrated a unique early pulmonary toxicity as discussed above ( 16 ). This risk can be reduced by commencing brigatinib at a lower dose 90 mg for 7 days before increasing to 180 mg daily if tolerated ( 34 ). If symptomatic pulmonary toxicity is suspected, brigatinib should be withheld pending prompt investigation and management.…”
Section: Discussion/summarymentioning
confidence: 99%